Gangguan Kecemasan Sosial Pada Remaja Dan Terapi Perilaku Kognitif Berbasis Internet Sebagai Pengobatan Masa Depan: Sebuah Studi Cross-Sectional - Septiana, Nila Zaimatus; Ramli, M.; Hidayah, Nur; Isrofin, Binti (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
Adolescents in social development are susceptible to social anxiety disorder (SAD). Adolescents need social support and self-acceptance in a social environment which in the process is often stressful to experience social anxiety. This study aims to identify social anxiety disorder in adolescents based on sociodemographic factors such as age, gender, family status, and residence as well as plans to use internet-based behavior therapy to be used as a treatment in future studies. This research approach is quantitative with a cross-sectional survey design. This study uses probability sampling with simple random sampling. The number of samples in this study is 458. This study used Social Anxiety Scale (SAC) questionnaire and data analysis using descriptive statistical tests, ANOVA tests, and Mann-Whitney tests. The results showed that the social anxiety category of adolescents was moderate, and only the age and place of residence had an effect on adolescent social anxiety. To overcome social anxiety, adolescents use internet-based Cognitive Behavior Therapy (I-CBT) as a future treatment.